Blood thiamin status and determinants in the population of Seychelles (Indian Ocean). Issue 4 (April 1998) - Bovet, P; Larue, D; Fayol, V; Paccaud, F
Abstract : STUDY OBJECTIVE: Micronutrient deficiencies have become rare in industrialised countries as availability of fresh food, supplementation, and fortification have improved but a less favourable situation may still prevail in many developing countries. Blood thiamin status and determinants were therefore investigated in the Seychelles in view of the high incidence of dilated cardiomyopathy and as the staple diet is polished rice that is deficient in thiamin. DESIGN: This was a cross sectional population study using an age and sex stratified random sample. SETTING: Seychelles Islands (Indian Ocean). PARTICIPANTS: A subsample of 206 subjects aged 25-64 years from the population of Seychelles. MAIN OUTCOME MEASURES: Measurement of total thiamin concentration in whole blood using high performance liquid chromatography. Dietary variables measured using a face to face semi-quantitative food questionnaire. RESULTS: Mean (SD) whole blood thiamin concentration was 77.9 (22.4) nmol/l and low concentration (< 70 nmol/l) was found in 37% of the subjects (95% CI: 31%, 44%). Blood thiamin was significantly related to education and diet but not to age, sex, smoking, and body mass index. Blood thiamin was associated positively with meat, vegetable, salad, and tea intake and negatively with alcohol and fish intake. However, no combination of the examined variables could explain more than 15% of the observed variance in blood thiamin values. CONCLUSIONS: These data suggest that the distribution of blood thiamin in the sampled population is shifted to lower values compared with that generally accepted as normal in European populations. Further research should establish the significance of such lower values in this specific population to facilitate clinical and public health action as necessary.